HUBUNGAN PERSEPSI DUKUNGAN SOSIAL DAN KETERPAPARAN MEDIA INFORMASI DENGAN PRAKTIK PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI DI SMAN 5 DEPOK - Ulpa Susanti (2020)
Breast self-examination (BSE) is a self-examination, by learning how to see changes in one's own breasts every month and developing a woman's concern for the condition of her own breasts. But in reality, awareness to do breast self-examination is still lacking among women. This study aims to analyze the relationship between perception of social support and information media exposure with the practice of breast self-examination (BSE) in adolescent girls STATE 5 DEPOK. This study uses a cross-sectional design. Respondents were selected using Probability sampling technique, namely sampling with a random sampling method of 169 respondents. The questionnaire was tested for validity and reliability. Chi square test results have a significant relationship between social perception perception with BSE practices (P =0,019), information media exposure (p = 0,001) with breast self-examination practices (BSE). Based on the results of the study found the implementation of community health tasks has an important role in acting as a good agent of change for health to provide BSE counseling to adolescents. Therefore, it is expected that respondents routinely make BSE once a month to detect cancer early.